Análise das respostas comportamentais de consumidores de duas sociedades com traços culturais distintos em um cenário de cocriação - Muratore, Nicole Speguem (My University, 2019)
The present study analyzes the behavior of the consumer inserted in an experimental scenario of co-creation in two groups with different cultural traits. For this purpose, a descriptive quantitative research was applied, which was operationalized through a questionnaire that, besides considering profile and consumption questions, investigated product engagement, anticipation of satisfaction and purchase intention, in the context of sneakers customization. The societies were chosen based on the spectrum of countries proposed by Hall (1989), on the classification of low and high context cultures. Therefore, it was chosen a country considered with a low-context cultural profile (United States) and a country with a high-context profile (Brazil). There were 405 valid cases distributed between the two countries (147 Brazilians and 258 North Americans), separated into four distinct groups: Brazilians that had previously experienced co-creation (34), Brazilians that had not previously experienced co-creation (113), North Americans that had previously experienced co-creation (71) and North Americans that had not previously experienced it (187). The results showed that Brazilians are significantly more engaged in comparison to North Americans. However, North Americans showed higher averages for anticipated satisfaction and purchase intention. In addition, it was observed that the fact that the consumer having previous experience of co-creation did not lead to different behavioral responses.(sic)
O presente estudo analisa o comportamento do consumidor inserido em um cenário experimental de cocriação em dois grupos com traços culturais distintos. Para tanto, foi aplicada uma pesquisa quantitativa de caráter descritivo, operacionalizada por meio de um questionário que, além de contemplar questões de perfil e de consumo, investigou engajamento, antecipação da satisfação e intenção de compra, no contexto de customização de um tênis. A escolha das sociedades baseou-se no espectro de países proposto por Hall (1989), sobre a classificação de culturas de baixo e de alto contexto. Portanto, foi escolhido um país considerado com perfil cultural de baixo contexto (Estados Unidos) e um país com perfil de alto contexto (Brasil). Foram obtidos 405 casos válidos distribuídos entre os dois países (147 brasileiros e 258 norte-americanos), estes separados em quatro subgrupos diferentes: brasileiros com experiência prévia de cocriação (34), brasileiros sem experiência prévia de cocriação (113), norte-americanos com experiência prévia de cocriação (71) e norte-americanos sem experiência prévia de cocriação (187). Os resultados apontaram que brasileiros são significantemente mais engajados em comparação aos norte-americanos. Contudo, os norte-americanos apresentaram médias mais altas com relação a antecipação da satisfação e a intenção de compra. Além disso, observou-se que o fato do consumidor ter experiência prévia de cocriação não conduziu a respostas comportamentais distintas. (sic)
Keywords: Consumidores; Comportamento do consumidor; Cultura